Metal Consumption of Heat Engines and Heat Capacity of their Working Fluids - Kiselev V.G.; Kalyutik A.A.; Kukolev M.I. (Problems of the Regional Energetics, 2020)
Ensuring efficient energy supply in general and heat supply in particular together with creation of air conditioning systems is a very urgent task of modern energy industry, particularly acute in the absence of large centralized energy sources. The cost of such systems is largely related to the cost of heat engines operating both in the direct and reverse cycle, in its turn determined by their construction and installation costs that are directly related to their metal consumption. Our goal was to reduce metal consumption of heat engines. It had been achieved with the use of thermo-dynamic potentials and thermodynamic cycles in conjunction with a model idea of the ideal gas, Carnot and Phillips heat engines, etc. The most significant result was mathematical formulas that for a given efficiency linked the heat capacity of the ideal gas with the geometric dimensions of heat engines under consideration, the working cylinder volume of the Carnot heat engine and the amount (volume) of metallic mesh participating in heat exchange with the working body of the Philips heat engine. Significance of these results lies in establishing a steady trend of reducing metal consumption of Philips and Carnot heat engines with a reduction in heat capacity of the ideal gas used as their working body. As Carnot and Philips cycles are model cycles used for analyzing other heat engines, including those utilizing real gas systems, this clearly shows the possibility of reducing metal consumption of real heat engines while reducing heat capacity of their working fluids.